Microstructure and fatigue properties of TC4 titanium alloy treated by α+β forging process. Issue 1 (May 2021) - Cui, Wenbin; Chen, Xuan; Cheng, Li; Ding, Junliang; Wang, Changkai; Wang, Bohan
Abstract: As aero engine life increases, blade fatigue has become one of the key factors restricting the high reliability and long service life of aero engine. In this paper, TC4 bar was treated by α+β forging process. The microstructure and mechanical properties of the treated material were observed and tested at room temperature, and the three point bending ultrasonic fatigue test was carried out. The results show that the S-N curve of the α+β forging material presents a double platform shape. The high cycle showed surface cleavage mode, the very high cycle showed internal cleavage mode, and the very high cycle cracks originated from the primary phase cleavage plane.